UTILIZATION OF SOCIAL CAPITAL IN ENHANCING THE VILLAGE DEVELOPMENT INDEX - Intan Dirjalaila; Badaruddin Badaruddin; Tengku Irmayani (Jurnal Kebijakan Publik, 2025)
The Village Development Index (Indeks Desa Membangun) is an instrument used to measure village progress and independence, with five status categories: very underdeveloped (sangat tertinggal), underdeveloped (tertinggal), developing (berkembang), advanced (maju), and independent (mandiri). This study examines the utilization of social capital to improve the Indeks Desa Membangun in Medan Krio Village, Sunggal Subdistrict, Deli Serdang Regency, North Sumatra Province. Social capital, encompassing trust, norms, and networks, is considered a crucial asset in supporting village development. Using a qualitative approach, this study analyzes the contribution of social interactions and community participation to the improvement of the Indeks Desa Membangun. The findings indicate that social capital in Medan Krio Village significantly enhances community participation in development programs and strengthens social bonds among residents. Moreover, social capital fosters a conducive and stable village environment, essential for successful village development. The study concludes by emphasizing the importance of strengthening social capital as an effective village development strategy.